Highly potent antagonists of luteinizing hormone-releasing hormone free of edematogenic effects. - Bajusz, S (1988)
To eliminate the undesirable edematogenic effect of the luteinizing hormone-releasing hormone (LH-RH) antagonists containing basic D amino acids at position 6, exemplified by [Ac-D-Phe(pCl)1,2,D-Trp3,D-Arg6,D-Ala10]LH-RH [Phe(pCl) indicates 4-chlorophenylalanine], analogs with D-ureidoalkyl amino acids such as D-citrulline (D-Cit) or D-homocitrulline (D-Hci) at position 6 were synthesized and tested in several systems in vitro and in vivo. HPLC analysis revealed that the overall hydrophobicity of the D-Cit/D-Hci6 analogs was similar to that of the basic D-Arg6 antagonists. In vitro, most of the analogs completely inhibited LH-RH-mediated luteinizing hormone release in perfused rat pituitary cell systems at an antagonist to LH-RH molar ratio of 5:1. In vivo, the most active peptides, [Ac-D-Nal(2)1,D-Phe(pCl)2,D-Trp3,D-Cit6,D-Ala10]LH-RH [Nal(2) indicates 3-(2-naphthyl)alanine] and its D-Hci6 analog, caused 100% inhibition of ovulation in cycling rats in doses of 3 micrograms and suppressed the luteinizing hormone level in ovariectomized female rats for 47 hr when administered at doses of 25 micrograms. Characteristically, these peptides did not exert any edematogenic effects even at 1.5 mg/kg. These properties of the D-Cit/D-Hci6 antagonists may make them useful clinically.